Measuring A Brain Comfort in Neuroarchitectural Research: A Structured Theoretical Study - Arinta, Rizka; Bachtiar, Vania Angeline; Anastasia, Linda (Universitas Atma Jaya Yogyakarta, 2026)
Comfort is a central objective in architectural design, yet it varies across individuals. This study proposes an evidence-based framework for assessing comfort through a neuroarchitectural approach by analysing neurological parameters. A meta-analysis of Scopus-indexed literature identified 111 relevant keywords from an initial set of 1,298, derived from 2,561 unique keywords in peer-reviewed studies published over the past decade that employed neurological indicators in neuroarchitecture. The findings indicate that comfort is not solely subjective but can be examined through measurable biological and neurological markers. The literature is organised into three main parameters: environmental simulation and spatial comfort, neurological instrumentation and brain signal processing, and emotional perception and sensory experience. Thematic content analysis and bibliometric mapping were conducted using OpenRefine, VOSviewer, and Biblioshiny. The synthesis reveals clear correlations between neurological responses and architectural elements such as natural lighting, spatial configuration, material texture, and environmental control. These parameters reliably capture the neurophysiological mechanisms underlying comfort in built environments, with perceptual and emotional responses identified as particularly critical. Overall, meta-analysis establishes comfort as an objectively quantifiable phenomenon and provides a foundation for adaptive and inclusive architectural design that supports mental health, cognitive performance, and well-being. Future research directions include experimental studies integrating virtual reality and real-time biometric monitoring to further explore brain–environment interactions.